2001
DOI: 10.2307/3285322
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Typing of Toxoplasma gondii Using Microsatellite Loci

Abstract: High-resolution typing of Toxoplasma gondii is essential to understand the effect of genetic differences among strains on the variation in disease manifestation and transmission patterns. Current typing methods discern 3 lineages with minimal within-lineage variation. Described here are 6 new variable loci. These loci, including a minisatellite and 5 microsatellites, were more polymorphic than allozymes, restriction fragment length polymorphisms, and sequence variation in introns. Most importantly, these loci … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…Whether the timing of the cross and/or clonal expansion turns out to be 100, 1000, or 10,000 years will likely require a Toxoplasma fossil and exhaustive genome-wide comparative analyses to produce more accurate genetic drift calculations. Remarkably little variation among archetypes has likewise been identified among highly polymorphic microsatellite loci, supporting the recent clonal expansion interpretation (Blackston et al, 2001; Ajzenberg et al, 2002; Lehmann et al, 2006). In aggregate, the data show that sexual reproduction has produced three parasite lines that represent recent clonal rockets in the domestic cycle.…”
Section: Population Geneticssupporting
confidence: 52%
“…Whether the timing of the cross and/or clonal expansion turns out to be 100, 1000, or 10,000 years will likely require a Toxoplasma fossil and exhaustive genome-wide comparative analyses to produce more accurate genetic drift calculations. Remarkably little variation among archetypes has likewise been identified among highly polymorphic microsatellite loci, supporting the recent clonal expansion interpretation (Blackston et al, 2001; Ajzenberg et al, 2002; Lehmann et al, 2006). In aggregate, the data show that sexual reproduction has produced three parasite lines that represent recent clonal rockets in the domestic cycle.…”
Section: Population Geneticssupporting
confidence: 52%
“…Microsatellite analysis is based on the DNA sequence length polymorphisms of short nucleotide tandem repeats. The tandem repeats in T. gondii are often simple, consisting of as few as 2 nucleotides (di-nucleotide repeats), and occur 2–20 times (Blackston et al 2001; Ajzenberg et al 2002 a , 2004). The MLST is based on DNA sequence polymorphisms including the SNPs, insertion and deletion of nucleotides in the sequence.…”
Section: Molecular Methods For the Detection And Identificationmentioning
confidence: 99%
“…It was concluded that T. gondii had a clonal population structure (Howe and Sibley, 1995). Since then, different sets of multilocus PCR-RFLP or microsatellite markers have been applied to epidemiological and population studies (Blackston et al 2001; Ajzenberg et al 2002 a , b , 2004, 2005; Lehmann et al 2004, 2006; Khan et al 2005 a , b ; Ferreira et al 2006, 2008; Su et al 2006). A key finding of these studies was that T. gondii isolates from South America were highly diverse and distinct from those of North America and Europe.…”
Section: Molecular Methods For the Detection And Identificationmentioning
confidence: 99%
“…1 In addition to 6 microsatellite markers (B18, TUB2, TgM-A, W35, B17, and M33) for genotyping, a seventh marker (M48) was included for further characterization. 1,2,16 The forward primers r were 5′-end-labeled with either 6-carboxyfluorescein (B18, TUB2, and M48), hexachlorofluorescein (TgM-A, W35, and B17), or 2,7′,8′-benzo-5′-fluoro-2′,4,7-trichloro-5-carboxyfluorescein (M33). For the multiplex PCR, the total volume of 25 µl comprised commercial master mix i in a final concentration of 1×, a 0.04-µM concentration of each primer, r 4 µl of DNA extract, and 5 µl of nuclease-free water.…”
Section: Characterization Of T Gondii Parasitesmentioning
confidence: 99%